2010
DOI: 10.1101/lm.1651910
|View full text |Cite
|
Sign up to set email alerts
|

Emotional memory persists longer than event memory

Abstract: The interaction between amygdala-driven and hippocampus-driven activities is expected to explain why emotion enhances episodic memory recognition. However, overwhelming behavioral evidence regarding the emotion-induced enhancement of immediate and delayed episodic memory recognition has not been obtained in humans. We found that the recognition performance for event memory differs from that for emotional memory. Although event recognition deteriorated equally for episodes that were or were not emotionally sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 30 publications
0
15
0
1
Order By: Relevance
“…Memories associated with a negative emotion are strongly encoded and more easily recollected than those that do not have a particularly strong associated emotion142425. Event memory in the MVA context may have been more strongly encoded than that in the SAFE context.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Memories associated with a negative emotion are strongly encoded and more easily recollected than those that do not have a particularly strong associated emotion142425. Event memory in the MVA context may have been more strongly encoded than that in the SAFE context.…”
Section: Discussionmentioning
confidence: 97%
“…During the encoding task714, subjects were required to watch fourteen 10-s movie clips. Seven of these showed a SAFE and 7 showed a MVA accompanied by real sounds heard through headphones.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the interaction between amygdala-driven and hippocampus-driven activities explains how emotion enhances episodic memory recognition. 22 The behavioral evidence regarding the emotion-induced enhancement of immediate and delayed episodic memory recognition remains poorly understood in humans. However, this data may offer an explanation of how music-induced improvement of memory in surgical motor performance is mediated in the brain.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore analyzed the role of Zn 2+ and that of glutamate receptors in a form of learning involving the memorization of an event with a strong emotional component and so likely to be acquired at once and to remain permanently associated with the context in which it occurred (Kuriyama et al 2010), thus constituting episodic-like memory, a form of autobiographical declarative memory which is referred to as flashbulb memory. As in our previous studies, we chose fear conditioning, a form of Pavlovian conditioning that can be achieved in a single session (Phillips and LeDoux 1992;Daumas et al 2007).…”
mentioning
confidence: 99%